Associations of lifestyle and diet with the risk of nasopharyngeal carcinoma in Singapore: a case–control study. Issue 1 (December 2017) - Yong, Sook; Ha, Tam; Yeo, Ming; Gaborieau, Valerie; McKay, James; Wee, Joseph
Abstract Background Nasopharyngeal carcinoma (NPC) is a commonly diagnosed cancer in Southeast Asia. Many studies have examined the risk factors for NPC, yet the roles of some risk factors remain inconclusive. The purpose of this study was to examine associations between modifiable lifestyle factors and the risk of NPC in the Singaporean population. Methods We conducted a case–control study in Singapore with 300 patients and 310 controls who were recruited between 2008 and 2012. Each control was selected and individually matched to each patient based on sex, ethnicity, and age (±5 years). A total of 290 pairs of cases and controls were matched successfully. We examined lifestyle factors such as tobacco smoking, alcohol drinking, various salted and preserved food consumption, and weaning practices. Results After adjusting for covariates, multivariate analysis showed that those participants who were current smokers and had ever smoked tobacco had a higher risk of NPC than participants who had never smoked, with odds ratios (ORs) of 4.50 (95% confidence interval [CI] 2.58–7.86;P  < 0.001) and 2.52 (95% CI 1.54–4.12;P  < 0.001), respectively. Those who consumed salted vegetables at least once a week also showed a significantly increased risk of NPC than those who never or rarely consumed salted vegetables, with an OR of 4.18 (95% CI 1.69–10.38;P  = 0.002). Conclusion Smoking (currently and ever-smoked) and consuming salted vegetables once a week or more were lifestyle risk factors for NPC, and changes of these factors for the better may reduce the risk of NPC.